The Moral Element of the Crime of Genocide and the Challenges of Proving “It Palestinian Case Study” - shtayah, Mohammad (Journal of Legal Sciences, 2026)
This research aims to study the moral element in the crime of genocide, especially the special criminal intent in this intentional crime, and the challenges that make proving it extremely complex in the Palestinian case. This research followed the descriptive analytical approach. The research problem lies in the main question: How can the moral element, especially the special intent, in the crime of genocide be identified and proven in the context of the Palestinian situation? What are the challenges of applying the rules of evidence associated with it? The research reached the following conclusions: The moral element is considered the essential element in describing the crime of genocide, especially proving the special criminal intent that distinguishes it from other international crimes. Proving the moral element, especially special criminal intent, in the crime of genocide requires adopting an approach that combines behavior analysis, government policies, military documents, and speeches of incitement. The study recommends calling on the Palestinian Ministry of Foreign Affairs, in cooperation with the Ministry of Justice, to establish a national body for international criminal documentation that would collect evidence related to international crimes, particularly genocide, in accordance with the procedural and evidentiary rules adopted before the International Criminal Court. Calling on the Palestinian Ministry of Justice and the International Crimes Prosecution to prepare comprehensive legal files on the crime of genocide, based on evidentiary evidence derived from an analysis of the inflammatory rhetoric of Israeli leaders and officials, the long-standing policies adopted against the Palestinian people, and the patterns of criminal acts. Calling on the State of Palestine to form international alliances with countries that support the rights of the Palestinian people and international justice to confront the Israeli narrative and break the political hegemony that Israel uses to justify genocide.